The role of heritage tourism in attracting "active" in-migrants to "low amenity" rural areas. Issue 2 (3rd May 2016) - Vuin, Ana; Carson, Doris Anna; Carson, Dean Bradley; Garrett, Jaimee
Abstract : Tourism can influence in-migration to rural areas by enhancing the attractiveness of rural communities and providing opportunities for employment, entrepreneurship and volunteer engagement appealing to in-migrants. Much research on the rural tourism-migration nexus has focused on "high amenity" areas characterized by scenic environments and well-developed tourism and service infrastructures. Many communities in inland Australia, however, are in "low amenity" areas where tourism opportunities are limited to exploiting industrial and cultural heritage assets. This article examines the role of heritage tourism in facilitating in-migration to such areas based on interviews with in-migrants to three communities in South Australia's Mid-North, focusing on the experiences of "active" in-migrants who get economically or socially involved in their new communities. Findings suggest heritage tourism minimally affected migration decisions. Key attractors were housing, employment, cost of living and easy access to the city. Business opportunities in tourism were attractors where the tourism industry was relatively well developed. Overall, the factors influencing in-migration differed among communities suggesting locally, not regionally, focused place marketing strategies are required to target in-migrants.